APPLICATION OF NOVEL NATURAL MUCOADHESIVE POLYMER IN THE DEVELOPMENT OF PENTOXIFYLLINE MUCOADHESIVE TABLETS - JOHN SELVARAJ, GNANASEKARAN; BALASUBRAMANIAN, ARUL; RAMALINGAM, KOTHAI (International Journal of Applied Pharmaceutics, 2019)
Objective: The present study was planned to develop a mucoadhesive tablet formulation of the drug pentoxifylline using natural mucoadhesive polymer from the plant Ocimum basilicum Linn. Methods: The isolated polymer was used to formulate the mucoadhesive tablets with 3 different concentrations. The tablets were formulated by using direct compression technique and evaluated for various parameters such as thickness, friability, weight variation, hardness, mucoadhesive strength, swelling index by standard methods, and the in vitro drug release studies in USP dissolution test apparatus type-II. Results: The swelling index was indirectly proportional to the polymer concentration and the tablets with a high concentration of polymer showed better mucoadhesive strength (28.5532±0.4660). The in vitro drug release showed that the drug release was indirectly proportional to the polymer concentration. The formulation F3 showed the controlled release of drug pentoxifylline (99.84±1.86) for 10 h. The mechanism of drug release was found to be Fickian diffusion and followed the zero-order kinetics, which was proved by its highest linearity (r2) in all the formulations. Conclusion: The tablets formulated with the isolated polymer of Ocimum basilicum Linn showed the good mucoadhesive mucoadhesive property and it controlled the release of the pentoxifylline.